An Analysis for Credit Rating and Momentum Strategy - Wang, Mu-Lan; Wang, Ching-Ping; Lee, Shiang-Yi (Asian Economic and Financial Review, 2015)
In recent years, investors are increasingly concerned about whether the credit risk will affect the return on investment. This paper discusses the credit rating and momentum investment strategy relationship. The research period is from January 2005 to December 2010, and the sample is the ordinary shares of companies listed on Taiwan Stock Exchange (TSE). By calculating the cumulative returns of the investment portfolio of the holding period, and grouping the research samples by credit rating, this paper tests the relationship between credit rating and momentum investment strategy in Taiwan’s stock market. Second, in the exploration of the factors affecting credit rating and stock returns, this paper uses variables including firm size, financial leverage, turnover rate, company age and industry to analyze the impact of factors including information asymmetry and industry on the investment strategy. Moreover, this paper probes into the impact of January Effect and business cycle on credit rating. The empirical results reveal that Taiwan’s stock market does not have the momentum effect, although there is reverse investment strategy. In other words, the returns of stocks of investment portfolio of better credit rating are higher than those of poorer credit rating; and the results are reverse if the reverse investment strategy is applied. The empirical results are not affected by adding variables such as firm size, financial leverage, turnover rate, company age and industry. Hence, momentum investment strategy of Taiwan’s stock market is not affected by credit rating.